Effect of Acetylsalicylic Acid on Microvascular Thrombosis in Autologous Breast Reconstruction - Enajat, Morteza; Aziz Mohammadi, Mujzgan; Debeij, Jan; van der Hulst, Rene R. W. J.; Mureau, Marc A. M. (Journal of Reconstructive Microsurgery, 2014)
Although advances in microsurgery have increased success rates of autologous breast reconstruction, microvascular thrombosis still remains a major concern as a cause of flap failure. At present, no evidence-based guidelines on pharmacological prevention of microvascular thrombosis exist. This study investigates the effect of acetylsalicylic acid on the incidence of microvascular complications in patients undergoing autologous breast reconstruction.Patients undergoing deep inferior epigastric artery perforator or free transverse rectus abdominis myocutaneous flap breast reconstruction at two academic centers in the Netherlands between 2005 and 2011 were included. Patients at one center received once daily 0.6 mL of nadroparine and 40 mg acetylsalicylic acid, while patients at the other center received 0.6 mL nadroparine only.A total of 430 consecutive patients underwent 592 breast reconstructions. No statistically significant differences were found between the two groups in the incidence of flap failure (2.8 and 2.5%), microvascular thromboembolic complications (2.6 and 3.8%), venous congestion (3.4 and 2.8%), or overall complications (28.0 and 32.3%). Hematoma tended to occur more often in the group receiving acetylsalicylic acid (9.2 and 4.7%).It was found that no protective effect of acetylsalicylic acid on microvascular complications was present. Given its known risks and the somewhat increased occurrence of hematoma in the present study, we stopped to routinely administer acetylsalicylic acid after autologous breast reconstruction.
Keywords: DIEP; TRAM; breast reconstruction; acetylsalicylic acid; thrombosis